ASSESSING PREVALENCE AND FACTORS ASSOCIATED WITH CESAREAN DELIVERY AMONG WOMEN OF REPRODUCTIVE AGE IN NIGERIA - Bamigbala, Olateju Alao; Ojetunde, Ayodeji Oluwatobi; Ibrahim, Abdulmudallib (FUDMA JOURNAL OF SCIENCES, 2022)
Cesarean section (CS) involves the fetus, membranes, and placenta delivery through abdominal and uterine incisions after fetal viability. Some research on CS use in Nigeria have been undertaken, however, they have all been institutional-based and had small sample sizes. In the country, nationally representative studies on this critical issue are required. As a result, the current study assesses prevalence and factors associated with cesarean delivery among women of reproductive age in Nigeria. The data used in this study were sourced from the 2018 Nigeria Demographic and Health Survey (NDHS). 8216 women of childbearing age were considered in this study. The 2018 survey is the most recent in Nigeria's series of NDHS (at the time of this study). The methods of analysis used for this study are frequency, percentage, chi-square test, and Binary Logistic Regression Analysis. Statistical software used for the analysis was STATA V.15. p<0.05 was considered to be statistically significant. The prevalence of CS in Nigeria was 8.1% in 2018. Factors associated with increased odds of CS were maternal age (35-39 years), the South West regions of Nigeria, urban residency, wealth index (rich), previous terminated pregnancy, less than 9 months of pregnancy, and maternal education (secondary education). The findings will give evidence-based knowledge for decision-making in Nigeria regarding the provision and use of cesarean birth. However, improved availability and access to obstetric care services should be pursued further by following the WHO's EOC guidelines in all Nigerian regions.